Factors influencing diffusion of activity based costing in institution of higher education / Hazlina Hussein - Hussein, Hazlina (2012)
Activity Based Costing (ABC) was first introduced in the manufacturing industries and has gradually been evolving in other industries such as services as well. Malaysia, being one of the education hubs in Asia must work on controlling costs and address high quality education issue at the same time. For this purpose, universities need to find and adopt a tool or system which can link and enable the accounting data to be used in formulating university's strategic plan to remain effective and efficient. This study was motivated from the intention to find out the possibility of diffusing Activity Based Costing (ABC) as one of the Strategic Management Accounting (SMA) innovation in the Institution of Higher Education (IRE). The sampling was carried out accordingly and samples were taken from two institutions in two different sectors, i.e. private and public. Using the diffusion theory and ABC as the SMA innovation, the present study investigates the relationship and the influence of the contextual variables, (environments, organisation and information technology), towards the implementation of ABC in IRE. The results from the Pearson Correlation show that ABC can be diffused in IRE based on the innovation characteristics of the diffusion theory. The present study found that the implementation of ABC in IRE is affected by the environmental and organisation factors but not by IT.